Nutritional and Functional Characteristics of Coconut Water-Based Soy Sauce Enriched with Gonggong (Strombus turturella): A Novel Fermented Health Product - Hazimah Hazimah (Information Technology and Science (ITScience), 2025)
The use of coconut water as a fermentation substrate in making soy sauce is a sustainable innovation in the food industry. This study aims to evaluate the nutritional characteristics, physicochemicals, and functional potential of soy sauce formulated using coconut water and the addition of gonggong meat (Strombus turturella), a type of marine mollusk rich in protein and minerals. The fermentation process was carried out for 14 days using tempeh yeast as a source of proteolytic enzymes. The parameters analyzed included pH, total soluble solids (°Brix), protein content, sodium, antioxidant activity, and organoleptic tests. The results showed a significant increase in protein content (2.67 g/100 ml) and antioxidant activity (57.4%) compared to the control soy sauce. The addition of gonggong provides a savory taste profile and a distinctive marine aroma that is preferred by panelists. This product has the potential as an alternative to low-soy functional soy sauce, is allergy-friendly, and supports the use of local resources. These findings open up opportunities in the development of marine-based fermentation products that support public health.